Consumption Patterns and Hanging-Out Culture in Shaping Students’ Purchasing Decisions in Surabaya - Hafsah Shufairaa; Nurul Hanifa (CV Pena Jaya Pers, 2026)
Purpose: This study examines how consumption patterns and hanging-out culture shape students’ purchasing decisions in Surabaya, addressing the limited attention to the socio-symbolic dimensions of student consumption in urban Indonesia. Design/methodology/approach: A qualitative phenomenological approach was employed to capture students’ lived experiences. Data were collected through in-depth interviews with eight university students selected using purposive sampling and analysed using thematic analysis to identify recurring meaning structures. Findings: The findings suggest that purchasing decisions are not primarily driven by economic rationality, but by the interaction of habitus, social context, and symbolic value. Two fluid consumption orientations emerge: social-oriented consumption and experiential consumption. The findings also indicate that students shift dynamically between these orientations depending on situational contexts, indicating that consumption behaviour is not fixed but relational and adaptive. Research limitations/implications: The study is limited by its qualitative scope and small sample size. Future research should incorporate mixed methods to examine the relationship between symbolic consumption and spending patterns quantitatively. Practical implications: The findings suggest that coffee shop strategies should move beyond price competition and focus on creating socially and symbolically meaningful experiences for student consumers. Originality/value: This study provides empirical insights into how Bourdieu’s concept of habitus operates in a fluid and situational manner within student consumption practices. Paper type: Research paper